Crimson Silks and New Potatoes: The Heteroglossic Power of the Object in Atwood's Alias Grace - March, Cristie (Studies in Canadian Literature, 1997)
Margaret Atwood's novel Alias Grace, by exploring the story of Grace Marks through an authorial mosaic that includes multiple characters' points of view, as well as journal entries, letters, and other bits of prose and journalism relevant to her trial, invites a reading through the lens of Bakhtin's theory of heteroglossia. In particular, various objects throughout Alias Grace provide instances of heteroglossic intersection, especially during the exchanges between Grace and Dr. Jordan and over the course of her trial. The irresolution created by competing systems of coding in these instances corresponds to what some have labelled Atwood's use of "feminist-dialogic" speech as a resistant language mode. This frustrated speech and the concept of heteroglossia allow for readings of objects within the novel as both closed and opened, ultimately offering a multiplicity of readings that creates a text as unbounded as the main character.